KREATIVITAS DAN INOVASI DALAM REDAKSI DIGITAL : KOMODIFIKASI BERITA MENJADI VIDEO PENDEK DI TIKTOK - Nurazizah, Amelia (Universitas 17 Agustus 1945 Surabaya, 2024)
This research highlights how creativity and innovation are crucial in today's digital era, where the traditional way of disseminating news has evolved to become more dynamic and interactive. The purpose of this study is to identify the commodification of digital news editors into short videos on TikTok The research method used is a literature study, which allows researchers to explore in depth the literature related to the use of TikTok as a new medium in the news industry. This study delves into the phenomenon of news commodification, specifically in their shift to the short video format on the TikTok platform. The results of this study stated that these changes not only affect the way news is consumed, but also force professionals in the media industry to adapt their skills by mastering video editing techniques, understanding platform algorithms, and developing creative perspectives to present relevant stories. Studies on content commodification highlight the transformation of news into short videos on TikTok, changing the way traditional media delivers information and influencing consumer interactions with news content. With a focus on appealing to audiences who prefer quick and visual consumption, news media are faced with the challenge of maintaining substance and accuracy in short content. The commodification of audiences through platforms like TikTok reflects the media's strategy of reaching younger generations with compelling video editing and writing skills, as well as a deep understanding of social media dynamics. The shifting role of journalists in the digital age demands adaptation to new technologies and the ability to create relevant content, reinforcing the need for new skills and deep understanding in an increasingly competitive media industry. Keywords: Commodification, News, Tiktok, Industrial Transformation